Using Computer Simulators for Teaching Macroeconomics at the Undergraduate Level - ANGELOV, Aleks; VASILEV, Aleksandar (Journal of Research in Educational Sciences, 2016)
The integration of technology in the educational process is becoming increasingly important for improving the 21st century student’s understanding and retention of academic material. Being able to readily apply the theory covered in class and to automatically receive immediate feedback is invaluable. And with gamification now permeating into nearly every area of our lives, computer games are proving to be an effective way to successfully engage any audience. Presently, there are only a few freely available macroeconomic simulators on the Internet which are suitable for undergraduate students. The two most prominent ones are the European Central Bank’s €conomia and the Chair the Fed game. But both of them focus solely on monetary policy. Thus, there is no educational simulator that allows students to examine the effects of fiscal policy. This is particularly problematic since Bulgaria and several other countries in the region, which are not part of the Eurozone, operate under a currency board, meaning that they do not have much control over their monetary policy, so the emphasis there is mainly on conducting fiscal policy. Hence, prof. Vasilev and I developed the “Keynesian Macroeconomic Simulator of Fiscal Policy”.
Keywords: fiscal policy; simulators; macroeconomic principles; teaching innovations; AS-AD framework